1970
DOI: 10.1021/ie50726a005
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Permeability in Porous Media

Abstract: Fontugne and Raimondo Latini are former graduate students of the above department.This paper was presented as part of the Symposium on Flow Through Porous Media, Washington, D. C.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…For specimens n  = 1, 4 the R values obtained are respectively 0.79 and 0.83, while for n  = 2, 3 the R values obtained are 0.27 and 0.51. Based on Guibert et al and Rice et al, where isotropy is suggested to be the case when R > 0.75 and 0.65 < R < 0.84 respectively, specimens n  = 1,4 are much closer to being isotropic (Guibert et al, 2015, Rice et al, 1970) has the largest variation between kminp,kintp and kmaxp and therefore exhibits the largest degree of anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…For specimens n  = 1, 4 the R values obtained are respectively 0.79 and 0.83, while for n  = 2, 3 the R values obtained are 0.27 and 0.51. Based on Guibert et al and Rice et al, where isotropy is suggested to be the case when R > 0.75 and 0.65 < R < 0.84 respectively, specimens n  = 1,4 are much closer to being isotropic (Guibert et al, 2015, Rice et al, 1970) has the largest variation between kminp,kintp and kmaxp and therefore exhibits the largest degree of anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…It may be noted that large values of h correspond to a rapid transfer of heat between the phases (LTE) and small values of h gives rise to relatively strong LTNE effects. Although the porous medium is anisotropic, the preferential orientation of the grains constituting the medium renders it isotropic in the direction parallel to the stratification (Rees [16], Rice et al [17]). For this reason, the porous medium could be taken as being horizontally isotropic.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Over one hundred measurements of the value of the permeability ratio, r k , have been collated by who, along with Rice et al (1970), have summarised and assessed the wide variety of techniques that have been employed for measuring r k in both cohesive and non-cohesive media. Whilst some r k values were reported to be greater than 10 and also some to be less than 0.5, these occurred for varved clays, rocks and shallow clays; where laminations, cracking and holes from plant roots or burrowing animals could have impacted on measurements.…”
Section: Anisotropy Measurementsmentioning
confidence: 99%